Environmental Hygiene and Risk of Inflammatory Bowel Diseases: A Systematic Review and Meta-analysis. Issue 9 (September 2016) - Cholapranee, Aurada; Ananthakrishnan, Ashwin N.
Abstract : Background: According to the hygiene hypothesis, individuals raised in a sanitary environment have a higher risk of developing inflammatory bowel diseases (IBD). However, results have been inconsistent. We conducted this systematic review of factors related to environmental hygiene and risk of IBD, Crohn's disease (CD) and ulcerative colitis (UC). Methods: A systematic search was performed on MEDLINE between 1980 and 2015 to identify studies of the association between IBD and contact with pets and farm animals, number of siblings, bedroom sharing in childhood, and access to personal toilet and hot water. Random- or fixed-effect meta-analyses were performed, and analysis further stratified based on ethnicity of the included cohort. Results: A total of 29 relevant studies were included. Having a pet (odds ratio [OR], 0.76; 95% confidence interval [CI], 0.63–0.88) and contact with farm animals was inversely associated with risk of IBD (OR, 0.45; 95% CI, 0.31–0.60). However, the strength of association with farm animals was statistically stronger in non-white cohorts (OR, 0.27; 95% CI, 0.02–0.53) than in white cohorts (OR, 0.55; 95% CI, 0.45–0.65) ( P = 0.028). Access to toilet (OR, 0.71; 95% CI, 0.56–0.85) and hot water (OR, 0.67; 95% CI, 0.44–0.89) was inversely associated with UC in non-white populations but not whites. Having more than 2 siblings was inversely associated with risk of CD. Conclusions: Several factors pertaining to reduced environmental hygiene are inversely associated with risk of IBD. However, underlying ethnicity influences susceptibility to the effect of these factors. Abstract : Supplemental Digital Content Is Available in the Text.Article first published online 2 August 2016.